Risk Management Analysis of Bus Transportation Application Using COBIT 4.1 - Resad, Setyadi; Handy, Nur Prabowo (2021)
The role of information technology in transportation increases, namely in enjoying transportation services. One way to provide the best service for a transportation company to customers is to provide a bus booking application service. One of the companies that offer service applications is a bus transportation application located in Yogyakarta. Because the application system is considered necessary, stakeholders need IT risk management for the bus booking application. The purpose of this research is to analyze the risk management of the bus transportation application. In measuring IT risk management, the author uses the Control Objective for information and Related Technology (COBIT) 4.1 domain Plan and Organize (PO) framework, especially PO9 (Assess and Manage IT risk). The analysis results show that if the bus transportation application is at level 2 in maturity level. It means that the company knows that there are problems that need resolving. Standard risk management in bus transportation applications tends to provide failed access in the progress of its service. The problem is solving individually and not yet at the integrated completion stage. In general, the application management approach needs to improve better management in the field of information technology.